2014
DOI: 10.1111/ppl.12263
|View full text |Cite
|
Sign up to set email alerts
|

High‐temperature inhibition of biosynthesis and transportation of anthocyanins results in the poor red coloration in red‐fleshed Actinidia chinensis

Abstract: In plants, the role of anthocyanins trafficking in response to high temperature has been rarely studied, and therefore poorly understood. Red-fleshed kiwifruit has stimulated the world kiwifruit industry owing to its appealing color. However, fruit in warmer climates have been found to have poor flesh coloration, and the factors responsible for this response remain elusive. Partial correlation and regression analysis confirmed that accumulative temperatures above 25 °C (T25) was one of the dominant factors inh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
42
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 56 publications
(44 citation statements)
references
References 53 publications
2
42
0
Order By: Relevance
“…The dominant anthocyanin peak had a molecular ion of m/z 581, while another peak had a molecular ion of m/z 499. The results indicated that cyanidin 3-O-xylo(1-2)-galactoside was the major anthocyanin present in ‘Hongyang’ fruit during storage, which is consistent with previous report in pre-harvest ‘Hongyang’ fruit (Man et al, 2015b). …”
Section: Resultssupporting
confidence: 92%
See 3 more Smart Citations
“…The dominant anthocyanin peak had a molecular ion of m/z 581, while another peak had a molecular ion of m/z 499. The results indicated that cyanidin 3-O-xylo(1-2)-galactoside was the major anthocyanin present in ‘Hongyang’ fruit during storage, which is consistent with previous report in pre-harvest ‘Hongyang’ fruit (Man et al, 2015b). …”
Section: Resultssupporting
confidence: 92%
“…Hasegawa et al (2001) reported that the mRNA level of DFR was significantly increased under low temperature condition, indicating the important role of DFR in the regulation of anthocyanin biosynthesis. In recent, Man et al (2015b) found that both ‘early’ and ‘late’ structure genes, including CHS, CHI, F3H, DFR1, LDOX , and F3GT2 showed higher expression in ‘Hongyang’ kiwifruit grown in high altitude with lower temperature compared to low altitude area. Moreover, they also found that expressions of CHS, CHI, F3H, DFR, LDOX, ANR , and FLS were inhibited at 40°C compared with that at 25°C in harvested ‘Hongyang’ kiwifruit (Man et al, 2015a).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Anthocyanin biosynthesis in A. chinensis var. chinensis red-fleshed fruit is associated with expression of MYB10 (also known as MYB1) Man et al 2015), although at this stage it has not been shown to determine the red phenotype in segregating populations.…”
Section: Transcriptional Regulationmentioning
confidence: 99%